The effect of Aerva anata (linn) ethanol extract on implantation sites and endometrial thickness of female mice (Mus musculus) - Nurul Fadhliati Maulida; Rajuddin Rajuddin; Yusra Septivera; Rusnaidi Rusnaidi; Muslim Akmal; Hafizuddin Hafizuddin; Lalu Muhammad Irham, M.Farm., Ph.D; Ilker Ates; Rockie Chong (Pharmaciana, 2026)
Aerva lanata (Linn.) contains secondary metabolites with antifertility potential, such as alkaloids, tannins, saponins, steroids, and flavonoids. The increasing need for accessible, cost-effective, and reversible contraceptive options further underscores the importance of investigating plant-based antifertility agents such as Aerva lanata. This study evaluated the effects of ethanol extract of A. lanata on implantation sites and endometrial thickness in female mice (Mus musculus L., Swiss Webster). Using a posttest-only control group design, five treatment groups (200, 400, 800, and 1000 mg/kgBW) and a control group received daily extract administration for 10 days. On day 12 of pregnancy, mice were sacrificed to count implantation sites and measure endometrial thickness. Statistical analysis by ANOVA followed by Duncan’s Multiple Range Test revealed that the 800 mg/kg and 1000 mg/kg groups showed complete inhibition of implantation (100% anti-implantation activity; p< 0.05). Additionally, the endometrial thickness was significantly reduced from an average of 150 ± 10 µm in control mice to 85 ± 8 µm and 70 ± 7 µm in the 800 and 1000 mg/kgBW groups, respectively (p < 0.05). These dose-dependent reductions in implantation and endometrial thickness suggest that the ethanol extract of A. lanata is a promising antifertility agent in female mice.